2021
DOI: 10.1016/j.clinre.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in COVID-19 inpatients: Incidence and management in a multicenter experience from Northern Italy

Abstract: Highlights UGIB has a prevalence of 0.47% in non-ICU COVID-19 patients and peptic disease is the most common finding. Half of patients were managed conservatively or with delayed endoscopy. This is the first report that evaluates incidence of UGIB in COVID-19 patients. Conservative management and delayed endoscopy could be a successful option in patients with significant respiratory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
2
24

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 28 publications
3
88
2
24
Order By: Relevance
“…Certainly, the small sample size might have also influenced the result. In Northern Italy, the most common cause of UGIB was peptic ulcer disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the small sample size might have also influenced the result. In Northern Italy, the most common cause of UGIB was peptic ulcer disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mauro et al. 46 described 11 patients who had active peptic ulcers, erosive gastritis and bleeding from gastro-oesophageal varices. A summary of the reported investigation findings and treatments used are provided in Table 3 .…”
Section: Management Of Covid-19-related Gi Manifestationsmentioning
confidence: 99%
“…Despite the presence of fibrinolysis shutdown in a significant proportion of patients with COVID-19, bleeding complications, including hemorrhagic stroke 56 and gastrointestinal bleeding, 57 are not uncommon and deserve special consideration. A systematic review and meta-analysis of hospitalized patients with COVID-19 reported a 7.8% overall pooled incidence of bleeding with 3.9% comprising major bleeding complications.…”
Section: Thrombotic and Bleeding Complica-tions In Covid-19-associated Fibrino-lysis Shutdownmentioning
confidence: 99%